2016
DOI: 10.1089/ten.tea.2015.0230
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Implantation of NELL-1 Enhances Bone Formation in an Osteoporotic Sheep Model

Abstract: Our findings suggest rhNELL-1-based vertebral implantation successfully improved cortical and cancellous bone regeneration in the lumbar spine of osteoporotic sheep. rhNELL-1-based bone graft substitutes represent a potential new local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…An improved bone quality was detected by microtomographic investigations as BMD significant increase in a dose-dependent manner in defects treated with rhNELL-1 in comparison with control as well as BV/TV and Tb.N showed a significant increase at both dosages. The histomorphometric analysis further confirmed the results obtained with microCT, highlighting an improved cortical and cancellous bone regeneration [61].…”
Section: Large Animal Modelsupporting
confidence: 80%
“…An improved bone quality was detected by microtomographic investigations as BMD significant increase in a dose-dependent manner in defects treated with rhNELL-1 in comparison with control as well as BV/TV and Tb.N showed a significant increase at both dosages. The histomorphometric analysis further confirmed the results obtained with microCT, highlighting an improved cortical and cancellous bone regeneration [61].…”
Section: Large Animal Modelsupporting
confidence: 80%
“…Recently, an interstitial 11p14.1-p15.3 deletion involving the Nell-1 gene was also reported in associated with short stature in children [ 16 ]. Moreover, it was demonstrated that the NELL-1 has potential roles as a bone-forming growth factor in sheep [ 47 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an interstitial 11p14.1-p15.3 deletion involving the Nell-1 gene was also reported in associated with short stature in children [32]. Moreover, it was demonstrated that the NELL-1 has potential roles as a bone-forming growth factor in sheep [33].…”
Section: Potential Independent Of Positive Selection In the Dbp Populmentioning
confidence: 97%